Altered GABAergic markers, increased binocularity and reduced plasticity in the visual cortex of Engrailed-2 knockout mice - Allegra, Manuela; Genovesi, Sacha; Maggia, Marika; Cenni, Maria C.; Zunino, Giulia; Sgadò, Paola; Caleo, Matteo; Bozzi, Yuri (Frontiers in Cellular Neuroscience, 2014)
The maturation of the GABAergic system is a crucial determinant of cortical development during early postnatal life, when sensory circuits undergo a process of activity-dependent refinement. An altered excitatory/inhibitory balance has been proposed as a possible pathogenic mechanism of autism spectrum disorders (ASD). The homeobox-containing transcription factor Engrailed-2 (En2) has been associated to ASD, and En2 knockout (En2-/- ) mice show ASD-like features accompanied by a partial loss of cortical GABAergic interneurons. Here we studied GABAergic markers and cortical function in En2-/- mice, by exploiting the well-known anatomical and functional features of the mouse visual system. En2 is expressed in the visual cortex at postnatal day 30 and during adulthood. When compared to age-matched En2+/+ controls, En2-/- mice showed an increased number of parvalbumin (PV+), somatostatin (SOM+) and neuropeptide Y (NPY+) positive interneurons in the visual cortex at P30, and a decreased number of SOM+ and NPY+ interneurons in the adult. At both ages, the differences in distinct interneuron populations observed between En2+/+ and En2-/- mice were layer-specific. Adult En2-/- mice displayed a normal eye-specific segregation in the retino-geniculate pathway, and in vivo electrophysiological recordings showed a normal development of basic functional properties (acuity, response latency, receptive field size) of the En2-/- primary visual cortex. However, a significant increase of binocularity was found in P30 and adult En2-/- mice, as compared to age-matched controls. Differently from what observed in En2+/+ mice, the En2-/- primary visual cortex did not respond to a brief monocular deprivation performed between P26 and P29, during the so-called “critical period”. These data suggest that altered GABAergic circuits impact baseline binocularity and plasticity in En2-/- mice, while leaving other visual functional properties unaffected.